2021
DOI: 10.1016/j.neuroimage.2021.118219
|View full text |Cite
|
Sign up to set email alerts
|

Brain network reorganization after targeted attack at a hub region

Abstract: The architecture of brain networks has been extensively studied in multiple species. However, exactly how the brain network reconfigures when a local region, particularly a hub region, stops functioning remains elusive. By combining chemogenetics and resting-state functional magnetic resonance imaging (rsfMRI) in an awake rodent model, we investigated the causal impact of acutely inactivating a hub region (i.e. the dorsal anterior cingulate cortex) on brain network properties. We found that suppressing neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 76 publications
(100 reference statements)
4
25
0
3
Order By: Relevance
“…5 ). These spatiotemporal coactivation patterns triggered by dHP calcium spikes clearly suggest that DMN is indeed a functional network with coordinated activity between separate nodes ( Tu et al, 2021b , 2021a ).…”
Section: Discussionmentioning
confidence: 86%
“…5 ). These spatiotemporal coactivation patterns triggered by dHP calcium spikes clearly suggest that DMN is indeed a functional network with coordinated activity between separate nodes ( Tu et al, 2021b , 2021a ).…”
Section: Discussionmentioning
confidence: 86%
“…This approach was recently utilized by an awake rat resting-state fMRI database and derived similar results ( Liu et al, 2020 ). The metric was built on robust cingulate and RSC FC, as both are considered to be key nodes of the DMN ( Tu et al, 2021a ; Tu et al, 2021b ; Peeters at al., 2020 ; Belloy et al, 2021 ; Coletta et al, 2020 ; Grandjean et al, 2020 ; Paasonen et al, 2018 ; Lu et al, 2012 ), whereas the cingulate and somatosensory FC is usually low ( Gozzi and Schwarz, 2016 ), or often in opposing states ( Belloy et al, 2018 ; Gutierrez-Barragan et al, 2019 ). Nevertheless, emerging studies have shown dichotomous involvement of cingulate cortex in both the DMN and the SN ( Tsai et al, 2020 ; Mandino et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…The qEEG z-NF protocol in children with developmental dyslexia was combined with training for the various visual deficits in dyslexia, and it could positively affect the functional connectivity of a specific frequency network that is also involved in the reading process. The selective inhibition of the excitatory neurons in a brain hub (region) can change the network integration [57]. Reduced network integration can result from the selective suppression of the excitatory neurons in a hub.…”
Section: Introductionmentioning
confidence: 99%